A kish graphitic lithium-insertion anode material obtained from non-biodegradable plastic waste. (15th January 2016) - Sri Devi Kumari, T.; Jebaraj, Adriel J.J.; Raj, T. Antony; Jeyakumar, D.; Kumar, T. Prem
Abstract: Graphitic carbon continues to dominate as the choice anode material in lithium-ion batteries despite its theoretical specific capacity of 372 mAhg −1 . Tailored forms of graphite with higher practical capacities should, therefore, be of interest to the industry. This paper reports the production of a kish graphitic anode material from polyvinyl chloride by simultaneous carbonization of the polymer and dissolution of the resulting carbon in an iron melt to produce a supersaturated solution of carbon in iron, and subsequent precipitation of the carbon as graphite upon cooling. Our study presents a process for converting non-biodegradable plastic wastes that litter our surroundings into a technologically useful product. The new material exhibits a first-cycle reversible capacity of 444 mAhg −1 and sustains at least 200 cycles at C/10 rate before its capacity drops below 372 mAhg −1 . Highlights: Non-biodegradable plastic converted into anode material for lithium-ion batteries. PVC-derived kish graphite shows nanostructured carbon forms embedded in it. The graphite gives a first-cycle capacity of 444 mAhg −1 and sustains >500 cycles. The product is thermally more stable than a commercial lithium battery graphite. Possibility of converting plastic waste into a technologically useful product.